2023
DOI: 10.1155/2023/1329061
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Proteomics of Oral Mucosa Tissue to Identify Potential Biomarkers That Can Flag Predilection of Precancerous Lesions to Oral Cell Carcinoma: A Preliminary Study

Abstract: Oral squamous cell carcinomas are mostly preceded by precancerous lesions such as leukoplakia and erythroplakia. Our study is aimed at identifying potential biomarker proteins in precancerous lesions of leukoplakia and erythroplakia that can flag their transformation to oral cancer. Four biological replicate samples from clinical phenotypes of healthy control, leukoplakia, erythroplakia, and oral carcinoma were annotated based on clinical screening and histopathological evaluation of buccal mucosa tissue. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This structure serves as a molecular companion to control cellular growth and programmed cell death, while also preserving the cellular redox balance [ 2 , 13 ]. Studies have indicated that there is a significant level of Prx1 exhibits significant expression in different types of tumors, such as HNSCC [ 14 ], non-small-cell lung cancer [ 3 ], triple-negative breast cancer [ 15 ], esophageal cancer [ 16 ], CRC [ 4 ], and many others [ 17 ]. Prx1 is closely associated with tumor cell proliferation, apoptosis, senescence, invasion, metastasis, and prognosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This structure serves as a molecular companion to control cellular growth and programmed cell death, while also preserving the cellular redox balance [ 2 , 13 ]. Studies have indicated that there is a significant level of Prx1 exhibits significant expression in different types of tumors, such as HNSCC [ 14 ], non-small-cell lung cancer [ 3 ], triple-negative breast cancer [ 15 ], esophageal cancer [ 16 ], CRC [ 4 ], and many others [ 17 ]. Prx1 is closely associated with tumor cell proliferation, apoptosis, senescence, invasion, metastasis, and prognosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%